The Psychology Underlying Biased Forecasts of COVID-19 Cases and Deaths in the United States - Shefrin, Hersh (Frontiers in Psychology, 2020)
This paper discusses the impact of a series of psychological phenomena on the U.S. response to COVID-19, focusing on forecasts of cases and deaths. The specific phenomena comprise unrealistic optimism bias, overconfidence, anchoring and adjustment, representativeness, motivated reasoning, and groupthink.